1995
DOI: 10.1002/mc.2940130407
|View full text |Cite
|
Sign up to set email alerts
|

A human factor that recognizes DNA substituted with 2‐chloroadenine, an antileukemic purine analog

Abstract: 2-Chloro-2'-deoxyadenosine (cladribine), an analog of deoxyadenosine, is an important new drug for the treatment of hairy cell leukemia and other forms of adult and pediatric leukemia. By a gel-shift binding assay, we identified an activity in HeLa nuclear extracts that recognizes and binds to oligonucleotides substituted with 2-chloroadenine (ClAde). The activity was specific for ClAde residues because control oligomers did not readily compete out the complex. The binding factor was a monomeric protein that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The nucleotide inhibits ribonucleoside diphosphate reductase (25), DNA polymerases ␣ and ␤ (26), DNA ligase, and is incorporated into DNA (27). Together, these actions lead to the progressive accumulation of DNA single-strand breaks (20).…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide inhibits ribonucleoside diphosphate reductase (25), DNA polymerases ␣ and ␤ (26), DNA ligase, and is incorporated into DNA (27). Together, these actions lead to the progressive accumulation of DNA single-strand breaks (20).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are thought to increase the fidelity of nucleotide incorporation at the polymerase active site (23), or to disrupt the water structure within the minor groove of B-DNA and create a larger minor groove width at the polymerase active site (24). The similarities between pol ␤ and Taq polymerase are of interest in light of our previous study in which we found that pol ␤ also could not bypass a template CldAMP residue under our standard in vitro DNA synthetic conditions (10). Thus, the presence of the chlorine group on Ade projecting out into the minor groove most likely prevents or modifies the above protein side chain-to-polymerase contact sites.…”
Section: Discussionmentioning
confidence: 90%
“…Because CIdATP is not an absolute chain terminator for polymerase a, it is likely that its incorporation into cellular DNA will have significant effects on additional rounds ofDNA synthesis and enzymic processes. Indeed, we recently demonstrated that template ClAde residues were also in vitro blocks to DNA synthesis by human polymerases a and , (Hentosh and Grippo, 1994). These findings together with the above results may explain, in part, the reduced cellular DNA synthesis and may contribute to the cytotoxic action of CldAdo.…”
Section: Introductionmentioning
confidence: 99%